Flexible bi-layer terahertz chiral metamaterials. (20th July 2015) - Sonsilphong, Amornthep; Gutruf, Philipp; Withayachumnankul, Withawat; Abbott, Derek; Bhaskaran, Madhu; Sriram, Sharath; Wongkasem, Nantakan
Abstract: Thin and flexible bi-layer terahertz chiral metamaterials are experimentally demonstrated in both handednesses at terahertz frequencies. The structures are made of conjugated C8 metallic resonators fabricated on a flexible polyimide substrate. These structures exhibit chirality and can distinguish circularly polarized waves at the frequency range from 0.5 to 0.9 THz, equivalent to 57.15% bandwidth. The structures can be used as circular polarizers for terahertz waves.